Ethical entropy in public life - Iyer, V.R. Krishna (1995)
"Starting off with outlining the nature of our polity, the author refers to the developments which are seriously corroding our polity. He suggests remedying the situation through kindling passionate patriatism among the people, drawing full support from our women and youth power"
Keywords: Public administration - India; Ethics - India; Political philosophy - India; Political philosophy